Behavioral Sciences and Dentistry: A Working Marriage - Ganikos, Mary L.; Espin, Oliva M. (Canadian Journal of Counselling and Psychotherapy, 2012)
This article describes a model of interpersonal training- fordentists in which counselors have been involved. The authors discuss theneed for such training: and an approach to it developed at the Universityof Florida. This approach is based on the Carkhuff model for interpersonaltraining with variations to adapt it to the special needs of dentists.